WOMEN IN POWER: AN ANALYTICAL STUDY OF LEGISLATIVE PARTICIPATION AND POLITICAL REPRESENTATION IN HARYANA - Kumar, Sunil; Sonika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the status and dynamics of women’s legislative representation in Haryana, situating it within the broader discourse on gender and political participation in India. Drawing on electoral data from 1967 to 2024, the research highlights trends in women’s candidature, party-wise distribution, and socio-economic as well as educational profiles of elected legislators. The findings reveal that while women’s representation has increased over time, peaking at 13 MLAs in both 2014 and 2024, their overall share in the 90-member Assembly remains under 15%, signaling persistent underrepresentation. A critical insight emerging from the study is the dominance of political lineage and socio-economic privilege in enabling women’s entry into politics, with limited space for leaders from grassroots and marginalized backgrounds. Party-level strategies, though pivotal, often reflect symbolic rather than substantive inclusivity. Despite these challenges, the presence of women legislators has contributed to greater visibility, policy influence, and gradual shifts in social perceptions of gender and leadership. The paper concludes with recommendations for structural reforms, party-level commitments, and grassroots empowerment to translate representation into meaningful political participation and social transformation.